Nocturnal variation of the zooplankton community in coral reef substrates at Isla del Coco National Park (Eastern Tropical Pacific) - Esquivel-Garrote, Octavio (2020)
Introduction: Zooplankton is a major link in coral reef food webs and a source of nutrients for corals. Demersal zooplankton in coral reefs makes diel migrations at night to avoid predation by fish and corals, increasing abundance and biomass at night. Objectives: To study the composition and variation of the demersal and pelagic zooplankton community at night and to increase the taxonomic knowledge of the benthic copepod fauna over different substrates of a coral reef. Methods: Traps made of plastic, with a 100 μm mesh size collector cup attached, were placed for 12 hours between 5-10 m depth over four substrates: (1) sand, (2) small and (3) big colonies of Porites lobata, and (4) dead and alive corals. Sampling started at dusk (1800 h), and the collector cups were collected and replaced at 2100 and 0000, and the last samples removed at down (0600 h). Results: The highest abundance of zooplankton was capture over P. lobata colonies between 0000 to 0600 h. Copepods (adults, copepodites, and nauplii) dominated the community structure and were more abundant during all the time intervals and substrates. Pelagic copepods were more abundant than the benthic, however, not more diverse. Among the benthic copepods, 20 new records of harpacticoids and calanoids were registered for Isla del Coco and Costa Rican waters. Appendicularians and decapod larvae were also abundant. Changes in coral reef community structure were related with time and not with the kind of substrate, although some taxa were found only in a specific time interval or substrate. Conclusions: Community structure and abundance of demersal and pelagic coral reef zooplankton in Chatham Bay were dominated by copepods, larvaceans and decapod larvae, similar to other coral reefs around the world. The highest abundance peak of organisms in the water column between 0000 to 0600 h could be related to diel migration.